Menentukan Topik Skripsi Mahasiswa Dengan Menggunakan Relasi Fuzzy Intuisionistik - Raden Sulaiman; Rudianto Artiono; Budi Rahajeng (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2022)
One of the problems that often occurs isÂ  the students cannot complete the thesis as expected. One of the factors that always occurs is that the students choose or determine the topic of their thesis that is not in accordance with their competence. He is more likely to choose supervisor.Â  This article is the result of research that aims to determine the suitability of a student's thesis topic according to their academic competence. The research was conducted on Unesa Mathematics students who are at the fourth year. The number of subjects are 35 students who were at the beginning of semester 7 and at that time were taking a mathematics seminar course. Seminar courses are the beginning of the preparation of their thesis. The method used is a modification of the "Medical Diagnostic" method in the health, which uses the application of the intuitionistic fuzzy relation concept. The results showed that there were 13 students or only 43.3% whose choice of thesis topic was in accordance with their competence, there were 17 students or 56.7% whose choice of thesis topic was not in accordance with their competencies.